Penerapan IoT (Internet Of Thing) Pada Sistem Monitoring Dan Kontrol Aquarium Berbasis Web Service - Haikal, Muhammad; Mursyidah, Mursyidah; Nasir, Muhammad (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2023)
Monitoring and control in the aquarium , one of which is monitoring the condition of fish feed and water turbidity conditions in the aquarium. The usual method currently used is to monitor and control manually, namely by coming directly to the aquarium which is carried out by the owner of the ornamental fish themselves. This of course arises a problem, namely it takes a lot of energy and time to maintain and care for the health of the water and aquarium feed at all times. So that the owners cannot leave the activity, which causes the control and observation to be ineffective and inefficient. Therefore, an application Internet of Thing -based aquarium monitoring and control system web service. In the test method using response testing of tools and websites. From the test results, the average bandwidth obtained by observing packet loss is 10.73, at delay 5.13 and at jitter 8.22, the total bandwidth is 8.02918 during the process of sending information data.Keywords— Raspberry Pi, monitoring dan kontrol, aquarium, webservice, MQTT